Nitrogen-doped hollow carbon spheres derived from amination reaction of fullerene with alkyl diamines as a carbon catalyst for hydrogenation of aromatic nitro compounds - Sun, Y.; Cao, C.; Liu, C.; Liu, Jian; Zhu, Y.; Wang, X.; Song, W. (Pergamon, 2017)
© 2017 Elsevier Ltd Hollow carbon nanospheres have received much interest by virtue of the special shape, low density and large interior void space, allowing their many potential applications. Here we report a template-free route to produce nitrogen-doped hollow porous carbon spheres (denoted as N-HPCSs) through amination reaction of C60with alkyl diamines and subsequent carbonization. The size of wall thickness and cavity of hollow carbon spheres could be easily regulated by the chain length of alkyl diamines. After carbonization in Ar atmosphere, the obtained N-HPCSs exhibited excellent activity and recyclability for hydrogenation of aromatic nitro compounds with hydrazine hydrate. The facile approach presented in this work provides a new way for preparation of doped hollow porous carbon spheres.